Allenamides: A Powerful and Versatile Building Block in Organic Synthesis - Lu, Ting; Lu, Zhenjie; Ma, Zhi-Xiong; Zhang, Yu; Hsung, Richard P (Chemical reviews, 2013)
Lu et al examine allenamides with regard to being a building block in organic synthesis.